2010
DOI: 10.4051/ibc.2010.2.4.0010
|View full text |Cite
|
Sign up to set email alerts
|

Field Study on the Mycotoxin Binding Effects of Clay in Oreochromis niloticus Feeds and Their Impacts on the Performance as Well as the Health Status throughout the Culture Season

Abstract: Total aflatoxin and ochratoxin were detected in 3 naturally contaminated fish feed samples using immune-affinity method. The results revealed that the average levels of aflatoxins in the 3 examined samples were (15, 22 and 12 µg/kg) respectively while the average levels of ochratoxins were (15, 6 and 6 µg/kg). The results of determination of the effects of clay as a mycotoxin binder on the health status and performance of Oreochromis niloticus in comparing with a control group revealed that the survival rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Thus, the present study was designed to address this potential limitation of DDGS inclusion in aquafeeds. However, our results do not agree with observations reported by Abdelaziz et al (2010) and Agouz and Anwer (2011), who found substantial increases in fish performance when mycotoxin binder products were included in mycotoxin-contaminated feeds. Possible reasons for these differing results include differences in (1) the types and levels of mycotoxins examined and (2) the mycotoxin deactivators utilized.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the present study was designed to address this potential limitation of DDGS inclusion in aquafeeds. However, our results do not agree with observations reported by Abdelaziz et al (2010) and Agouz and Anwer (2011), who found substantial increases in fish performance when mycotoxin binder products were included in mycotoxin-contaminated feeds. Possible reasons for these differing results include differences in (1) the types and levels of mycotoxins examined and (2) the mycotoxin deactivators utilized.…”
Section: Discussioncontrasting
confidence: 99%
“…Possible reasons for these differing results include differences in (1) the types and levels of mycotoxins examined and (2) the mycotoxin deactivators utilized. In our study, the mycotoxins present in the HPDDG sample were deoxynivalenol and zearalenone, whereas Abdelaziz et al (2010) and Agouz and Anwer (2011) evaluated fish feed that was contaminated with aflatoxin and ochratoxin. Additionally, the calculated mycotoxin levels based on the 24% HPDDG inclusion level in the current study were 0.6 g/g for deoxynivalenol and 410 ng/g for zearalenone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vitamin E contained in Fero Bind Pro had antioxidant activity and was associated with aflatoxin metabolism reduction [8]. Moreover, clays in general, were early used for their adsorptive properties to reduce the toxic effects of aflatoxins and ochratoxin [53] in O. niloticus . As well as Quillaja ( Quillaja saponaria ) if used in small amount of extracts improves weight gain and food utilization in tropical fish carp and tilapia [54].…”
Section: Discussionmentioning
confidence: 99%